Bank of Japan Equity Purchases: The (Non-)Effects of Extreme Quantitative Easing. (15th October 2020) - Charoenwong, Ben; Morck, Randall; Wiwattanakantang, Yupana
Abstract: From January 2011 through March 2018, the Bank of Japan purchased equity index exchange-traded funds (ETFs) worth about 3.5% of GDP. Identification of the effect of central bank ETF purchases on stock valuations and corporate responses is via differently-weighted and changing stock indices. BOJ purchases lift valuations, increase share issuances, and increase total assets. On average, the latter increase is due to cash and short-term securities rather than capital investment. However, firms with worse corporate governance do increase capital investment. These findings suggest central bank equity purchases are a problematic tool for stimulating economic growth through high broad-based private-sector corporate investment.